Bach's fight for freedom - Dykstra, Ted.; Labine, Kyle.; Clark, Ian D.; Dunsmore, Rosemary; Jubinville, Kevin; Petty, Ross, 1946-; Peterson, Eric, 1946-; Bach, Johann Sebastian, 1685-1750.; Devine, David; Mozer, Richard; Gillard, Stuart; Storey, Raymond; et al. (Toronto : Devine Entertainment, 2002)
Set in 1717, Johann Sebastian Bach's boss, Duke Wilhelm has given him a servant that Bach thinks is a spy. However, the temperamental composer soon realizes that his new assistant, 10-year-old Frederick, also knows what it is like not to be able to follow your dreams.
Special features: Historical notes -- Expanded soundtrack -- Language: English Dolby digital stereo ; Spanish Dolby digital stereo ; French Dolby digital stereo --Subtitles: English.
DVD; Dolby Digital stereo.
English, Spanish, French.
Closed captioned.
Title from disc surface.
Ted Dykstra, Kyle Labine, Ian D. Clark, Rosemary Dunsmore, Kevin Jubinville, Ross Petty, Eric Peterson.
Music, Johann Sebastian Bach ; created and story by David Devine, Richard Mozer ; screenplay, Raymond Storey ; producers, David Devine, Richard Mozer ; director, Stuart Gillard ; director of photography, David Perrault ; editing, Michael Pacek.
Keywords: Bach, Johann Sebastian, -- 1685-1750 -- Drama; Bach, Johann Sebastian, -- 1685-1750 -- Juvenile drama; Composers -- Germany -- Drama; Composers -- Germany -- Juvenile drama; z -- idex; Children's films; Feature films; Fiction films; Biographical films; Video recordings for the hearing impaired